2008
DOI: 10.1371/journal.pbio.0060246
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Differentiation of Adult Hippocampal Neurons Is Crucial for Spatial Memory

Abstract: Adult neurogenesis in the dentate gyrus plays a critical role in hippocampus-dependent spatial learning. It remains unknown, however, how new neurons become functionally integrated into spatial circuits and contribute to hippocampus-mediated forms of learning and memory. To investigate these issues, we used a mouse model in which the differentiation of adult-generated dentate gyrus neurons can be anticipated by conditionally expressing the pro-differentiative gene PC3 (Tis21/BTG2) in nestin-positive progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
175
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(187 citation statements)
references
References 92 publications
6
175
0
6
Order By: Relevance
“…To summarize, a clear disruption of trace eye-blink conditioning has been described (Shors et al 2001(Shors et al , 2002, whereas conflicting results have been reported for contextual fear conditioning. Although some studies reported impairment in generating and/or retrieving contextual fear memory Winocur et al 2006;Farioli-Vecchioli et al 2008;Imayoshi et al 2008;Wojtowicz et al 2008;Deng et al 2009;Hernandez-Rabaza et al 2009), opposite results were found in other studies (Shors et al 2002;Clark et al 2008;Dupret et al 2008;Kitamura et al 2009). …”
Section: Causationmentioning
confidence: 87%
“…To summarize, a clear disruption of trace eye-blink conditioning has been described (Shors et al 2001(Shors et al , 2002, whereas conflicting results have been reported for contextual fear conditioning. Although some studies reported impairment in generating and/or retrieving contextual fear memory Winocur et al 2006;Farioli-Vecchioli et al 2008;Imayoshi et al 2008;Wojtowicz et al 2008;Deng et al 2009;Hernandez-Rabaza et al 2009), opposite results were found in other studies (Shors et al 2002;Clark et al 2008;Dupret et al 2008;Kitamura et al 2009). …”
Section: Causationmentioning
confidence: 87%
“…Numerous studies have employed various methods of ablating neurogenesis in the hippocampus and have reported resultant deficits across a range of hippocampal-dependent cognitive tests including contextual fear conditioning (Farioli-Vecchioli et al, 2008;Saxe et al, 2006;Winocur et al, 2006), trace conditioning (Shors et al, 2001), Morris water maze (MWM) (Dupret et al, 2008;Snyder et al, 2005), object location task (Goodman et al, 2010) and delayed non-matching to sample task (Winocur et al, 2006). Of particular significance is that some studies controlled for hippocampal-independent tasks and found that ablation of neurogenesis did not impair performance in these tasks including cued fear conditioning (Farioli-Vecchioli et al, 2008;Saxe et al, 2006), delay conditioning (Shors et al, 2001) and the cued MWM (Snyder et al, 2005). Furthermore, Niibori et al (2012) reported that ablation of hippocampal neurogenesis (by chemical and genetic methods) resulted in impaired spatial discrimination of similar, but not dissimilar, contexts.…”
Section: Adult Hippocampal Neurogenesis and Cognitive Functionmentioning
confidence: 99%
“…Within 2 months, the surviving neurons receive inputs (van Praag et al, 2002;Piatti et al, 2006), form functional synapses with their target cells (Toni et al, 2008), and exhibit electrophysiological properties indistinguishable from those of mature neurons (Ge et al, 2007). These adult-born neurons are integrated into existing networks and play an important role in spatial memory (Dupret et al, 2008;Farioli-Vecchioli et al, 2008;Zhang et al, 2008;Garthe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%